Improving Learning Achievement Using Effective Mix and Match Learning Model - Rahmawati, Anis; Nurhidayati, Aryanti (Sebelas Maret University, 2016)
This current study aims to examine the implementation of the mix and match of three learning models i.e. Self-directed learning, Discovery learning, and Collaborative Problem Based learning. Mix and match learning model is performed to optimize the benefits from each models and minimize the weakness.Â In implementation phase, the learning process was started from self-directed learning models, where students were directed to collect any information regarding the subject from many resources using Web-based Instruction. This method basically involves encouraging students to prepare for the lesson before class. To complete this session, the student make a literature review. In the next session the Discovery learning models was implemented. In this session Picture Prompt presentation technique and some interactive experiences such as asking provocative questions were applied. After this, the Collaborative Problem Based Learning is performed using mix of several techniques i.e. Make a Match, Student Team Achievement Division and Number Heads Together. The Small group discussions model is a part of the Collaborative Problem Based Learning models. In the end of Collaborative learning session, the selected student presented their work. In the last session, every student has to make summarize using their own words. Assessments were performed in end of each session. The research found that the mix and match model effectively improve the studentâs achievement in cognitive, affective and psychomotor aspect.